ANALYSIS OF COST VARIATION OF ANTI-CANCER DRUGS - Bhandari, Prasan R. (Journal of Biomedical and Pharmaceutical Research, 2019)
Introduction: Indian pharmaceutical industry being one of the largest pharmaceutical markets in the world has a large number of branded formulations and generic brands of the same drug with a large difference in their selling price. The study was planned to find out variation in cost of  anti-cancer drugsMethods: Information was sourced from NETMED MOBILE APP. The drug formulation being manufactured by only one company or being manufactured by different companies; however, in different strengths would be excluded. Difference in the maximum and minimum price of the same drug formulation manufactured by different pharmaceutical companies and percentage variation in price would be calculated.Results: The maximum cost variation in the alkylating agents group was seen with Oxaliplatin 50mg/10ml (71.43%). In the antimetabolite group the maximum cost variation was seen in Gemicitabine 1000mg (357.67%). 68.7% cost variation was observed with Paclitaxel 30mg/5ml in the antimitotic natural products group. Doxorubicin 10mg/5ml showed the maximum cost variation in the cytotoxic antibiotic group as well amongst all the anticancer drugs. Within the targeted group imatinib 400mg showed the maximum cost variation i.e 505.20%.Conclusion: Thus, this study highlights that there is a significant price difference among the anti-cancer drugs manufactured by different companies. Hence stringent measures should be brought into implementation by the government and concerned agencies for uniformity in drug pricing.